Associations between individual perceptions of PM2.5 pollution and pulmonary function in Chinese middle-aged and elderly residents - Qi Chen; Jiayao Zhang; Yan Xu; Hong Sun; Zhen Ding (BMC, 2020)
Abstract Background PM2.5 pollution has become a major public health concern in urban China. Understanding the residents' individual perceptions toward haze pollution is critical for policymaking and risk communication. However, the perceptions of middle-aged and elderly residents, who particularly vulnerable to haze pollution, are poorly understood. In this study, we aimed to explore their risk perceptions of haze pollution and investigate its relationship with health status and pulmonary function parameters. Methods A cross-sectional study of 400 randomly sampled individuals (aged 40 to 90 years) was conducted in Wuxi, a typical PM2.5-polluted city in Jiangsu Province, China (during 2015-2017, daily average concentration of PM2.5 was 52.7 μg/m3). Each participant's demographic and health information, individual perception and pulmonary function outcomes were collected to explore the relationships between perception factors and personal characteristics and pulmonary function parameters, using linear models. Results We found that the mean values for controllability (5 ± 2.8) and dread of risk to oneself (levels of fear for haze-related harm to oneself) (6.9 ± 2.5) were the lowest and the highest values, respectively, in our study. Education and average family income were positively related with all individual perception factors, while age was negatively associated. A history of respiratory disease was positively associated with all individual perception factors except controllability. Significant positive associations were observed between PEF (coefficients ranged from 0.18 to 0.22) and FEF75% (coefficients ranged from 0.18 to 0.29) with a variety of individual perception factors. Conclusions There were a lack of concern and knowledge, weak self-protection consciousness and a strong dread of PM2.5 pollution among the middle-aged and elderly residents in Wuxi. Their individual perceptions were associated with age, education levels, average family income, history of respiratory disease, PEF and FEF75%. Our findings may help policymakers develop effective policies and communication strategies to mitigate the hazards of haze among older residents.